Analisis Strategi Pemasaran Pada PT Telkomsel Bandar Lampung - Vonny Tiara Narundana; Gilang Cahya Samudra (Universitas Mitra Indonesia, 2020)
AbstractTelkomsel leads by having the largest number of subscribers at 43% compared to its strict competitors, Indosat and XL. But by having enough customers, PT did not close. Telkomsel to stop looking for new customers or keep customers who are already using its products, with such behavior or strategy will affect the life of a company for a long time. The research objective is to analyze the marketing strategy at PT Telkomsel Bandar Lampung. The design of this research is descriptive (explanatory). The population is all employees and management of Telkomsel Bandar Lampung, amounting to 231 people and a sample of 70 people. The analysis is carried out with the SWOT Matrix which is used to compile the company's strategy. The results showed that PT Telkomsel Bandar Lampung is in quadrant I. This shows that PT Telkomsel Bandar Lampung is currently in the position of Growth and Build (growing and developing). Based on the company's position the appropriate alternative strategies used in this quadrant are intensive strategies (market penetration, market development, and product development) or integrative (backward integration, forward integration and horizontal integration). Keywords: Analysis, Marketing Strategy, PT Telkomsel.